2019
DOI: 10.1016/j.idcr.2019.e00577
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired liver abscess caused by capsular genotype K2-ST375 hypervirulent Klebsiella pneumoniae isolates

Abstract: Hypervirulent Klebsiella pneumoniae has been associated with community-acquired liver abscesses in relatively healthy subjects since the 1990s, occasionally accompanied by disseminated disease. While isolates of capsular genotype K1 belonging to sequence type (ST) 23 have been the most prominent causative pathogen of this syndrome, other virulent clones have been implicated sporadically in recent years. A 68-year-old woman with diabetes in Okinawa, Japan suffered from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In Taiwan, a hypervirulent K. pneumoniae (hvKP) variant was detected in 1986 for the first time, and these strains are increasingly being reported in Argentina, Korea, Australia, USA, and Scandinavia [1,2,[4][5][6][7][8]10]. HvKP may result in an invasive clinical syndrome, which is defined as a community-acquired liver abscess with or without extrahepatic complications like necrotizing fasciitis or endophthalmitis [9,13,14]. Furthermore, hvKP's infection has the ability to spread metastatically [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, a hypervirulent K. pneumoniae (hvKP) variant was detected in 1986 for the first time, and these strains are increasingly being reported in Argentina, Korea, Australia, USA, and Scandinavia [1,2,[4][5][6][7][8]10]. HvKP may result in an invasive clinical syndrome, which is defined as a community-acquired liver abscess with or without extrahepatic complications like necrotizing fasciitis or endophthalmitis [9,13,14]. Furthermore, hvKP's infection has the ability to spread metastatically [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, K1-ST23 has been recognized as the most prevalent HV-KP isolate from liver abscess, 4 and all reported cases of K2-ST375 infection showed the presence of liver abscess. [15][16][17] Therefore, these two strains may be more likely to cause lung abscess in addition to liver abscess and should receive attention as causative pathogens of lung abscess, although current data are limited.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Importantly, three of the five reported cases of K. pneumoniae K2-ST375 infection (60%), including the case described here, are from Okinawa Prefecture in Japan. [15][16][17] A nationwide molecular epidemiological study that did not include Okinawa Prefecture also reported that K2-ST375 was not isolated in the main islands of Japan. 13 Our patient was from Miyako Island, Okinawa, located near Taiwan-380 km west of Taiwan and situated on the same latitude-where HV-KP-induced lung abscess was first reported.…”
Section: Dovepressmentioning
confidence: 99%
“…To construct the phylogenetic tree for the collection under study, we first mapped the short-reads against the genome of the reference strain of K. pneumoniae Ecl8, a ST375/K2 hypervirulent clone of epidemiological significance causing severe community-acquired infections [ 36 ] (accession number: PRJEB401) [ 37 ] with the Snippy pipeline ( https://github.com/tseemann/snippy ) with default parameters. We then computed the pair-wise SNP distance between the strains and reconstructed the neighbor-joining phylogenetic tree using the ape (v5.7.1) package in R [ 38 ].…”
Section: Methodsmentioning
confidence: 99%